Governance as a Government Breakthrough to Improve Community Empowerment in SMEs in Makassar City - Cudai Nur, Andi; Sofia Rukmana, Novayanti; Sulmiah, Sulmiah; Nur Pratiwi, Oky; Nuraina, Asri (Indonesian Association for Public Administration (IAPA), 2024)
This study aims to determine the government's breakthrough in improving community empowerment to develop SMEs through entrepreneurship in an effort to improve community welfare and regional income. The research method refers to qualitative research with a focus on SME development strategies with entrepreneurship and community empowerment. The results of the study indicate that a professional digital-based SME governance strategy has been implemented by arranging, organizing or running, and controlling to develop the strength of the marketing and sales network, and being able to analyze the production network to improve product quality. Several policies have been established, including regional regulations that provide opportunities for SMEs to continue to develop the creativity and innovation of the community. Additional findings include the need for community involvement to be able to contribute to the empowerment of digital-based small and medium enterprises. Complementing the policy strategy by creating a SME governance formulation that is in accordance with the needs and dynamics of the development of local community life in Makassar City. The sustainability of the life cycle of SME organizations needs to be continuously improved through strengthening SME entrepreneurship, to optimize community empowerment in SME governance in Makassar City, South Sulawesi.